MENGUNGKAP FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN BELANJA DI KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM BALI TAHUN ANGGARAN 2020 - Putra, Nengah Jnana; Budiasih, I Gusti Ayu Nyoman; Ramantha, I Wayan; Asmara Putra, I Nyoman Wijana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p08, 2023)
This study aims to identify delays in budget absorption in the work units within the Bali Ministry of Law and Human Rights Regional Office and the factors causing it with goal setting theory as the foundation theory. This research is a qualitative research with a case study approach. In this research, the research site is the Regional Office of the Ministry of Law and Human Rights in Bali. Secondary data sources come from the Regional Office of the Ministry of Law and Human Rights in Bali and publications on the official website of the Ministry of Law and Human Rights of the Republic of Indonesia and the Directorate General of Treasury of the Ministry of Finance of the Republic of Indonesia. The primary data in this study were the results of direct interviews with research sources. The results of the study indicate that there is a tendency for delays in the absorption of budget expenditures in work units within the Regional Office of the Ministry of Law and Human Rights, Bali. The factors that cause delays in the absorption of the central government's budget are the Covid-19 pandemic, budget planning, procurement of goods/services, and human resources. Goal setting theory is a motivational theory that has an influence in achieving the performance targets that have been set.